Research of the peculiarities of plasma-electrolytic treatment of AK12M2MgN piston alloy with formation of ceramic-like coatings - Karakurkchi, Ann; Sakhnenko, Mykola; Ved, Maryna; Parsadanov, Igor (Technology audit and production reserves, 2017)
The object of research is the processes of the piston alloy AK12M2MgH treatment by the method of plasma electrolytic oxidation (PEO) with the formation of ceramic underlying coatings. One of the most problematic places is the influence of the chemical composition of the Al-Si alloy on the process of treatment and formation of ceramic coatings. It is established that electrochemical technologies are widely used to modify the surface of silumins by forming coating of various composition and purpose. In the course of the study it was shown that PEO of piston silumin should be carried out in alkaline complex electrolytes with the addition of manganese and/or cobalt salts. This makes it possible to homogenize the surface layer of the alloy by composition, to reduce the content of its alloying components and to create conditions for the formation of a uniform oxide coating with incorporation of the admissible components. It has been established that oxidation in pyrophosphate cobaltous solution allows obtaining mosaic structures of blue-violet color with cobalt content up to 24 at %. PEO silumin in the manganous alkaline electrolyte provides the formation of a brown-black ceramic-like layer with manganese content up to 35 at %. Consecutive PEO treatment in these solutions leads to the formation of a mixed fine-dispersed porous oxide coating with a total content of dopant 25–30 at %. Based on the research results, it has been proposed to oxidize the piston silumin in a regime of incident power to form uniform coatings with a high content of dopant. Obtained oxide systems have a developed surface and a significant content of catalytically active components. In comparison with the known methods of PEO treatment of piston silumin, the silicon content in the surface oxide layers does not exceed 3 at %, which is one of the requirements for catalytically active materials. The ceramics-like coatings show high catalytic activity in model oxidation reactions of CO and benzene and reduce the emission of toxic gas emissions from internal combustion engines. The proposed systems are promising for use in intracylindrical catalysis technologies and improving the fuel economy of engines.